THE DEMONSTRATION BIOGAS PRODUCTION FROM ORGANIC AND SECONDARY WASTE FROM AGRICULTURE - Петровић, Марија; Петровић, Предраг; Петровић, Мина (Economics of Agriculture, 2011)
In today's world, more attention to the development and application of biofuels, which can be produced from renewable primary and secondary agricultural commodities. However today are more developed procedures for the collection and production of biogas from various types of secondary organic waste, such as:communal and secondary utilities, wastes from the production of cereals and food, animal manure and others. The paper gives a short overview of the possibilities of production of biogas from organic waste, while at the same time as the solution to reduce waste disposal, and thus contribute to the development of ecological tourism and environmental protection.